Mengembangkan ChatBot Berbasis GPT dengan Pengetahuan Produk Internal - Muchlis (LPPM STMIK ANTAR BANGSA, 2024)
The implementation of ChatBot technology has become one of the popular solutions to improve human-machine interaction. Despite the many advantages offered by GPT-based ChatBots, the development of an effective implementation still poses several challenges. One of them is the lack of product knowledge that the ChatBot can possess. The use of a ChatBot without specific product knowledge often results in generic and uninformative responses, which may not properly address the user's needs or questions. Therefore, using BLACKBOX.AI, an advanced programming LLM, we aim to overcome this challenge by integrating product knowledge directly into the system. Integrating BLACKBOX.AI with the internal knowledge base can provide many benefits to the company, including improvements in service quality, operational efficiency, and overall user experience. This is an important step in improving the company's effectiveness and competitiveness in the ever-evolving digital era.